Fatal airbag-mediated atlanto-occipital dislocation in a child - Hassan, Radhiana; Mohd Yusof, Mubarak; Kamarudin, Norie Azilah (Universiti Sains Malaysia, 2010)
An atlanto-occipital dislocation is a rare airbag-induced injury in trauma patients. We report a case of an atlanto-occipital dislocation in a 6-year-old patient who was an unrestrained passenger in the front seat of a vehicle involved in a low-speed motor vehicle accident. This case illustrates the fatal threat of airbag deployment to the child passenger travelling in the vehicle front seat even in a low-speed collision, and supports the recommendation that children under 12 years of age travelling in vehicles with dual airbag systems should be seated in the back.